Associations among sources of revenue and expenses at public bachelors and masters level higher education institutions - Carmichael, John P., author; Kuk, Linda, advisor; Gloeckner, Gene, advisor; Bajtelsmit, Vickie, committee member; Foley, Jeffrey, committee member (Colorado State University. Libraries, 2015)
Understanding how changes in revenue are associated with changes in spending at public higher educational institutions may have significant practical implications for policy makers. Finance data were drawn from the Integrated Post Secondary Data System (IPEDS) for bachelors and master-level institutions from 2003 to 2012. Fixed effects regression models were constructed to estimate the effect of changes in revenue on spending. Time effects (lagged models, fixed year effects, and time trends) were examined. Several institutional characteristics were considered for inclusion in the model: size of enrollment, institutional discount rate, selectivity, Carnegie classification, and state tuition policy. In addition to revenue and spending variables, the final regression model included year effects and enrollment. A large number of statistically significant effects of revenue changes on spending variables were observed, generally consistent with previous research focused on research universities (Leslie, Slaughter, Taylor, & Zhang, 2012). The effects of changes in revenue from tuition and appropriations on spending for instruction were notable. Within an institution, a one dollar change in tuition revenue was associated with a 33 cent change in spending on instruction (2012 dollars). A similar one-dollar change in revenue from appropriations was associated with a 32 cent change in instructional spending. For spending on institutional support, a one-dollar change in revenue from appropriations had a slightly larger effect (β=.18, p<.001) compared to a one-dollar change in revenue from tuition (β=.07, p<.001).
Keywords: higher education finance